Pertautan Ontologi Filsafat dan Tasawuf: Telaah Relasi Tuhan, Manusia, dan Alam - Hadarah Rajab (Ulumuna, 2013)
Ontology dwells on the issue of how to explain substance, the nature of all that exists. Substance itself is an actual reality, not an artificial, deceiving, and changing reality. Since philosophy and mysticism are talking about substance, both fields of Islamic scholarship have a relationship to one another at an ontological level. This paper aims to elaborate interconnection between them. Elaborating the interconnection, the author analyzes the ontological aspects of al-Gazali’s sufism and Naqsyabandiah ṭarīqah. The author concludes that the ontological interconnection between both disciplines are very closely from the standpoint of the relation of God, man, and nature.